Testing Testing the Ability of Epiphytic Yeasts from Rice Leaves to Control Bakanae Disease in Rice Plants: Uji Kemampuan Khamir Epifit Asal Daun Padi untuk Pengendalian Penyakit Bakanae pada Tanaman Padi - Hrp, Rosiana Fadilah; Darnetty; Sulyanti, Eri (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2024)
Bakanae disease caused by Fusarium fujikuroi causes high yield losses ranging from 3.0-95.4%. The use of epiphytic yeast as a biocontrol agent has the potential to control F. fujikuroi. The aim of this research is to obtain epiphytic yeast species as potential biological control agents to suppress the growth of F. fujikuroi. This research will be carried out in two stages: isolation and in vitro screening. Isolation was carried out using the systematic sampling method and screening using several tests. The parameters observed were morphological characterization of epiphytic yeast and percentage of relative inhibition level against pathogen growth (%). The result showed that shape of the epiphytic yeast cells is round, oval, rod-shaped, and budding. The color of the colonies is pink, milky white, yellow and some form pseudomycelium. The results of observations of the hight percentage of relative inhibition levels against pathogen growth in three consecutive epiphytic yeast isolates were respectively KPSL1.11 (72,44 %), KPSL1.7 (61,37%) dan KPS3 (53,57%).